General Pharmacology of IY-81149, a New Proton Pump Inhibitor - Kim, Eun Joo; Lee, Rae Kyong; Lee, Seung Mok; Kim, Dong Yeon (Arzneimittelforschung, 2001)
IY-81149 (2-[(4-methoxy-3-methyl)2-pyridinyl]methylsulfinyl]-5(1-H-pyrrol-1-yl)-1H-benzimidazole, CAS 172152-36-2) is a new proton pump inhibitor and expected to be an antiulcer drug. Its general pharmacological effects were studied in this paper. The doses given were vehicle control, 0.3, 1, 3, 100, 300 and 1000 mg/ kg and were administered orally. The animals used in this study were mouse, rat, guinea pig and beagle dog. IY-81149 decreased spontaneous locomotor activity at 1000 mg/kg and showed a weak effect in motor performance at 300 and 1000 mg/kg. IY-81149 prolonged the hexobarbital induced sleeping time dose dependently at 100, 300 and 1000 mg/kg. Oral administration of IY-81149 caused a dose dependent hypothermic effect up to 300 mg/kg and showed analgesic effect at 1000 mg/kg. IY-81149 produced an anti-secretory effect in pylorusligated rats. The total gastric volume and acidity were significantly decreased at doses ranging from 1 to 3 mg/kg. However, IY-81149 had no effects on general behavior, did not show anticonvulsant activity, and did not affect blood pressure and heart rate, LVP (left ventricular peak systolic pres sure), LVEDP (left ventricular end diastolic pressure), LVDP (left ventricular developing pressure), DP (double product), HR (heart rate), CFR (coronary flow rate), smooth muscle contraction, respiration, intestinal transport and renal function. These findings demonstrate that IY-81149 possesses weak central nervous system action and inhibitory effects on microsomal enzymes and gastric secretion after single administration. The results suggest that IY-81149 does not exert any notable pharmacological effects on the cardiovascular system, autonomic nerve system or smooth muscle function at all doses tested.
Keywords: Antiulcer drug; CAS 172152-36-2; IY-81149, dog, general pharmacology, guinea pig, mouse, rat; (2-[(4-Methoxy-3-methyl)-2-pyridinyl] methylsulfinyl]-5-(1H-pyrrol-1-yl)-1H-benzimidazole; Proton pump inhibitor